1966
DOI: 10.1192/bjp.112.485.391
|View full text |Cite
|
Sign up to set email alerts
|

Some Experiments in the Chemistry of Normal Sleep

Abstract: Sleep is essential for physical and mental health. In the last 15 years there has grown up the concept of the brain stem reticular activating system. Electroencephalographic studies have shown two qualitatively different and alternating kinds of sleep, the orthodox (“slow wave”, or “forebrain“) and the paradoxical (”hind-brain“, “rapid eye movement”, “activated“, or “dreaming”) phases (Akert et al., 1965). It may be predicted that in the next decade attention will turn increasingly to the chemical basis of sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
1
1

Year Published

1967
1967
1984
1984

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(22 citation statements)
references
References 24 publications
1
19
1
1
Order By: Relevance
“…Smith & Prockop (1962) sent five of their seven patients to sleep during the day with a little over 6 g (-)-tryptophan but their experimental design was not balanced and did not control for temporal effects such as the increasing boredom of the participants. Another mood change that has consistently been found to occur with oral tryptophan is euphoria (Pollin, 1961;Smith & Prockop, 1962;Oswald, Ashcroft, Berger, Eccleston, Evans & Thacore, 1966). We were unable to demonstrate any such an effect with either intravenous or oral tryptophan.…”
Section: Discussioncontrasting
confidence: 41%
“…Smith & Prockop (1962) sent five of their seven patients to sleep during the day with a little over 6 g (-)-tryptophan but their experimental design was not balanced and did not control for temporal effects such as the increasing boredom of the participants. Another mood change that has consistently been found to occur with oral tryptophan is euphoria (Pollin, 1961;Smith & Prockop, 1962;Oswald, Ashcroft, Berger, Eccleston, Evans & Thacore, 1966). We were unable to demonstrate any such an effect with either intravenous or oral tryptophan.…”
Section: Discussioncontrasting
confidence: 41%
“…Claims that 1-tryptophan does not alter sleep stages as do the commonly used barbiturate and benzodiazepine hypnotics are supported by studies on small doses (1-5 grams) (Hartmann et al, 1974;Spinweber and Hartmann, 1978), although larger doses have been demonstrated to alter sleep stage parameters. While the reported direction of these stage alterations are conflicting for REM latency (Oswald et al, 1966;Wyatt et al, 1970) and REM time (Williams et al, 1969;Wyatt et al, 1970;Griffiths et al, 1972), the reports of effects of the larger doses on delta sleep (Stages 3 and 4) are consistent in demonstrating increases (Williams et al, 1969;Wyatt et al, 1970;Griffiths et al, 1972;Hartmann et al, 1974 the individual studies does not reach significance (Spinweber and Hartmann, 1978;Hartmann and Spinweber, 1979). …”
Section: L-tryptophan and Nocturnal Sleepmentioning
confidence: 99%
“…7, pp. 308-328 (Little Brown, Boston 1970 Results obtained with tryptophan are contradictory [Oswald et al 1966;Hartmann, 1967; Williams et al, 1969;Wyatt et al, 1970], but an increase in stage rapid eye movements (REM) has often been reported, especially with higher dosages [Williams, 1971]; there is, however, substantial agreement for an increase in REM sleep with 5-HTP [Mandell et al, 1964;Oswald et al, 1966;Wyatt et al, 1971], These data seem, in part, to conflict with those obtained with laboratory animals in which there has been observed an effect of 5-HTP upon NREM (non REM) sleep [Jouvet, 1969].It was considered to be of interest to investigate a possible modification by the two precursors upon the sleep pattern of schizophrenic subjects in view of the hypothesis of an altered metabolism of serotonin in schizophrenic syndromes. …”
mentioning
confidence: 99%
“…1966; Hartmann, 1967;Williams et al, 1969;Wyatt et al, 1970], but an increase in stage rapid eye movements (REM) has often been reported, especially with higher dosages [Williams, 1971]; there is, however, substantial agreement for an increase in REM sleep with 5-HTP [Mandell et al, 1964;Oswald et al, 1966;Wyatt et al, 1971], These data seem, in part, to conflict with those obtained with laboratory animals in which there has been observed an effect of 5-HTP upon NREM (non REM) sleep [Jouvet, 1969].…”
mentioning
confidence: 99%
See 1 more Smart Citation